The comparative burden of brain and central nervous system cancers from 1990 to 2019 between China and the United States and predicting the future burden - Jiajia Huang; Hanmei Li; Hualing Yan; Fen-Xiang Li; Mai Tang; Da-Lin Lu (Frontiers Media S.A., 2022)
BackgroundBrain and central nervous system (CNS) cancers represent a major source of cancer burden in China and the United States. Comparing the two countries' epidemiological features for brain and CNS cancers can help plan interventions and draw lessons.MethodsData were extracted from the Global Burden of Disease repository. The average annual percentage change (AAPC) and relative risks of cancer burdens were calculated using joinpoint regression analysis and age-period-cohort (APC) models, respectively. Moreover, a Bayesian APC model was employed to predict the disease burden over the next decade.ResultsFrom 1990 to 2019, the number of incidences, deaths, and disability-adjusted life-years (DALYs) increased in China and the US, with a larger increase in China. Age-standardized incidence rates in China and the United States have shown an increasing trend over the past three decades, with AAPCs of 0.84 and 0.16%, respectively. However, the rates of age-standardized mortality and age-standardized DALYs decreased in both countries, with a greater decrease in China. Overall, age trends in cancer burden were similar for males and females, with two peaks in the childhood and elderly groups, respectively. The period and cohort effects on incidence showed an overall increasing trend in China and limited change in the US. However, the period effects for mortality and DALY were decreasing in both countries, while the cohort effects tended to increase and then decrease. Moreover, we predicted that the cancer burdens would continue to rise in China over the next decade.ConclusionThe burden of brain and CNS cancers is substantial and will continue to increase in China. Comprehensive policy and control measures need to be implemented to reduce the burden.